Dinamika Lingkungan Sosial Digital dalam Pembentukan Perilaku Sosial Individu Generasi Z: Studi Literatur - Rida Sofia; Ellen Prima (INDO PUBLISHING, 2026)
The rapid development of digital technology and social media has transformed the social interaction patterns of Generation Z in various aspects of life. The digital social environment functions not only as a communication medium but also as a space for identity formation, social relationship development, and the internalization of social values and norms. This study aims to analyze the dynamics of the digital social environment in shaping Generation Z's social behavior, identify the dominant influencing factors, and explain the relationship patterns between digital social environments and social behavior based on contemporary literature. This research employed a literature study method using a systematic review approach of scholarly publications published between 2016 and 2026. Data were analyzed through identification, selection, evaluation, and thematic synthesis of previous studies. The findings indicate that digital social environments shape social behavior through self-presentation, social comparison, role models, and interactions with digital audiences. Dominant factors influencing social behavior include social comparison, social support, validation-seeking behavior, fear of missing out (FoMO), social media usage intensity, digital audience characteristics, and the quality of online interactions. Contemporary literature suggests that these relationships are dynamic, contextual, and non-linear because they are influenced by individual characteristics, social environments, and patterns of social media use. This study recommends strengthening digital literacy and developing more adaptive social media governance strategies for Generation Z.